SOME MATRIX MODELS - Garrão, Ana Paula; Dias, Margarida Raposo (European Scientific Journal, ESJ, 2015)
In this paper we present three matrix models that express the relevance of studying Linear Algebra, trying to answer the question Why study Linear Algebra?, often asked by students. Linear Algebra is fundamental within the mathematical modelling of phenomena, so we explore examples of models in which it is applied, in a simple manner as possible appropriated to the students’ knowledge. The models presented are Leontief Economic Model, Leslie Population Growth Model and Rating Web Pages Model.